2000
DOI: 10.1161/01.cir.101.24.2841
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A 1 Receptor Activation Induces Delayed Preconditioning in Rats Mediated by Manganese Superoxide Dismutase

Abstract: Background-We have previously described a second window of protection against infarction in rabbits 24 to 72 hours after adenosine A 1 receptor (A 1 R) activation. In this study, we examined the potential role of the mitochondrial antioxidant manganese superoxide dismutase (Mn-SOD) as a potential end effector in mediating this protection. Methods and Results-Rats were treated with an intravenous bolus of the A 1 R agonist 2-chloro-N 6 -cyclopentyladenosine (CCPA, 75 g/kg) or saline vehicle. They were also give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
2
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 58 publications
3
42
2
1
Order By: Relevance
“…Several studies have demonstrated a cardio-protective function for Hsp27, either through its exogenous overexpression from a transgene, or through its activation in preconditioning (25)(26)(27). In addition, this chaperone is known to contribute to preconditioning induced by a range of stimuli including opioids, isoproterinol, and ischemia (28)(29)(30). The protective effect of Hsp27 may include an anti-apoptotic role, which has been implicated in studies reporting an interaction of Hsp27 with cytochrome c and inhibition of apoptosome function (31).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a cardio-protective function for Hsp27, either through its exogenous overexpression from a transgene, or through its activation in preconditioning (25)(26)(27). In addition, this chaperone is known to contribute to preconditioning induced by a range of stimuli including opioids, isoproterinol, and ischemia (28)(29)(30). The protective effect of Hsp27 may include an anti-apoptotic role, which has been implicated in studies reporting an interaction of Hsp27 with cytochrome c and inhibition of apoptosome function (31).…”
Section: Discussionmentioning
confidence: 99%
“…Ser15 and Ser85 phosphorylation of Hsp27 by MAPKAPK-2 is the key mechanism in reduction of apoptosis and facilitation of F-actin remodeling that protects cells from doxorubicin toxicity (69). Further evidence for phosphorylation of Hsp27 having a role in myocardial protection is provided by studies on activation of the p44/42 MAPK (ERK1/2) and p38 MAPK pathways by atorvastatin (20) and on activation of the adenosine A 1 receptor and p38 MAPK (14).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that transgenic cardiac-specific overexpression of A 1 ARs would likely produce demonstrable changes in gene expression related to cardioprotective mechanisms based upon two lines of evidence: 1) delayed cardioprotection by preconditioning or A 1 AR activation relies upon de novo protein synthesis (3,16), which in turn is often dependent upon altered gene transcription; and 2) adenosine receptor activation has been shown to alter gene expression of atrial natriuretic peptide (ANP) (17), Na ϩ -I Ϫ symporter (6), MIP-1␣ (21), and IL-6 (19). In the current study, we have also demonstrated a decrease in the transcript level for MIP-1␣ and an increase in gene expression of preproANP with increased levels of adenosine receptors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the late phase of ischemic preconditioning new protein synthesis is required for cardioprotection (16). Furthermore, it has been demonstrated that adenosine-mediated delayed protection is dependent upon de novo protein synthesis (3). These changes in protein translation also result from changes in gene transcription.…”
mentioning
confidence: 99%